1996
DOI: 10.1212/wnl.46.5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Possible environmental, occupational, and other etiologic factors for Parkinson's disease

Abstract: In a case-control study, we investigated the possible etiologic relevance to Parkinson's disease (PD) of rural factors such as farming activity, pesticide exposures, well-water drinking, and animal contacts; toxicologic exposures such as wood preservatives, heavy metals, and solvents; general anesthesia; head trauma; and differences in the intrauterine environment. We recruited 380 patients in nine German clinics, 379 neighborhood control subjects, and 376 regional control subjects in the largest case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
277
7
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 384 publications
(306 citation statements)
references
References 36 publications
7
277
7
5
Order By: Relevance
“…In most studies of pesticides in relation to PD exposure was assessed retrospectively as a broad category, rather than examining specific substances. Of 38 case-control studies, 19 reported increased risk of PD [147,154,156,[289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] with ORs ranging between 1.3 and 3.7 for most studies. One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301].…”
Section: Case-control Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In most studies of pesticides in relation to PD exposure was assessed retrospectively as a broad category, rather than examining specific substances. Of 38 case-control studies, 19 reported increased risk of PD [147,154,156,[289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] with ORs ranging between 1.3 and 3.7 for most studies. One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Some case-control studies reported results for specific categories of pesticides, such as herbicides, insecticides, or fungicides, rather than pesticides overall. Of 18 studies that analyzed exposure to herbicides, 10 found increased risk of PD, either for herbicides as a group of substances, or for specific herbicides, such as paraquat, nitrile herbicides or 2,4-Dichlorophenoxyacetic acid [153,154,290,293,302,304,[321][322][323][324], with ORs ranging between 1.6 and 5.8. The other 8 studies reported no association between herbicides and PD [131,143,292,299,301,315,316,325].…”
Section: Case-control Studiesmentioning
confidence: 99%
See 3 more Smart Citations